Regime change within democracy? Intellectual discussions regarding the end of the French IV Republic (Colección, 2017)
This paper will attempt to elucidate a political moment: the passage from the IV to the V French République, which became exemplary for studies of political science that revolve around the "crisis of democratic regimes". However, the work will seek to clarify certain flaws of the explanation offered by the political science from a reconstruction of the actual political history and political / intellectual discussions that raised the event. In other words, the paper intends to contrast the classic political science understanding replenishing the historicity and the political nature of the event from the prism offering discussions among intellectuals.
Keywords: Regime; crisis; History; intellectuals